Footwork recognition and trajectory tracking in track and field based on image processing - Jiaju Zhu; Zhong Zhang; Runnan Liu; Junyi Liu (Scientific Reports)
Abstract In track and field sports, footwork can greatly affect the effect and performance of sports. Accurate footwork can effectively improve the performance of professional athletes, and for ordinary trainers, it can reduce the probability of training injuries. To solve the problem that traditional footwork is inaccurate and not well accepted by people, this paper has used an image processing method based on support vector machine (SVM) algorithm to identify and track the footwork. In this paper, a 13-s video image was extracted frame by frame from the athletes’ videos in Olympic sports competitions, and the athletes’ footwork was used as a benchmark to track their motion trajectories, extracting the corresponding feature points and categorizing them. 10 school athletes, 6 males and 4 females, were selected to track their movement pace and trajectory with a camera. The behaviors were standardized according to the extracted features, and the behaviors before and after standardization were compared. The results showed that the SVM algorithm had the most stable classification accuracy, higher recognition accuracy and better performance compared with other classification algorithms. Image processing of standardized track and field movements was effective in improving athletes’ performance, with all 10 athletes tested improving their performance between 0.4 and 0.6. The SVM algorithm-based image processing method is more acceptable after validation of its effectiveness, and the method can be extended more easily.